2019
DOI: 10.1001/jamainternmed.2018.5008
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Related Insulin Underuse Among Patients With Diabetes

Abstract: Role of the Funder/Sponsor: The Robert Wood Johnson Foundation had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; and decision to submit the manuscript for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
146
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 5 publications
3
146
1
Order By: Relevance
“…Results of these two studies suggest that while RCTs might show lower hypoglycaemia risk and improved pharmacokinetic/pharmacodynamic profiles of long‐acting insulins compared with intermediate‐acting insulins, such as NPH, these benefits may not translate to real‐life clinical practice. Furthermore, the higher cost of long‐acting BI analogues compared with human insulins may be an important factor to consider when selecting insulin therapies; for instance, one USA‐based survey conducted in an urban diabetes centre indicated that 25% of individuals with diabetes reported cost‐related underuse of insulin, and this was associated with significantly poorer glycaemic control …”
Section: Can Newer Bi Analogues Assist With Insulin Titration and Trementioning
confidence: 99%
“…Results of these two studies suggest that while RCTs might show lower hypoglycaemia risk and improved pharmacokinetic/pharmacodynamic profiles of long‐acting insulins compared with intermediate‐acting insulins, such as NPH, these benefits may not translate to real‐life clinical practice. Furthermore, the higher cost of long‐acting BI analogues compared with human insulins may be an important factor to consider when selecting insulin therapies; for instance, one USA‐based survey conducted in an urban diabetes centre indicated that 25% of individuals with diabetes reported cost‐related underuse of insulin, and this was associated with significantly poorer glycaemic control …”
Section: Can Newer Bi Analogues Assist With Insulin Titration and Trementioning
confidence: 99%
“…36 A study conducted at Yale University found that 25% of patients with diabetes ration insulin because of the high cost. 13,37 There are 30 million patients with diabetes in the United States, and approximately 25% (7.4 million Americans) need insulin. 14 For the 1.3 million patients with type 1 diabetes, insulin is as vital as air and water.…”
Section: Possible Solutions Solutions At the State And Federal Policymentioning
confidence: 99%
“…20 Indeed, insulin costs remain a singular point of tremendous focus in the diabetes cost landscape: consider that insulin prices increased 320% over the past 13 years 21 and that 1 in 4 patients reporting skipping insulin use due to cost from a recent single-center survey. 22 The heightened sensitivity and focus on insulin costs (among other types of drug costs) have led pharmaceutical companies to introduce generic versions, price caps, and pricing disclosures in consumer advertising, with mixed results. At the end of the day, the decoupling of the consumption of drugs versus its payment through insurance (for those with such coverage) mitigates the impact of pricing transparency on consumption decisions, among other factors.…”
Section: Diabetes Marketmentioning
confidence: 99%